Redesign Corporate Identity Guna Peningkatan Image Perusahaan Pada PT Yugi Indonesia - Dewi Immaniar Desrianti; Sugeng Santoso; Febri Adiputra (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2022)
In the increasingly rapid development of the business world, a corporate identity is needed that can represent the character of a company's business, product, or service. Corporate identity represented by the logo is an identity as a differentiator between each company. However, problems arise with the development of the times, the company realizes that the logo as a corporate identity that is made as a reflection of the vision and mission as well as the culture of a company becomes obsolete. From this condition, the step to redesign the corporate identity logo is considered to be a wise choice so that the logo as a corporate identity can communicate precisely with what is represented by the company. The purpose of this research discussion is the creation of a GSM book (Graphic Standard Manual) as a reference for designing a logo design which is a corporate identity that can be arranged systematically so that there are no more mistakes in its implementation to any visual media used by the company. In the study using a problem analysis method, data collection, design and media design concepts including rough layout, comprehensive layout, and final artwork, redesigning the logo design using Adobe Illustrator CC18 software. From designing the logo as a corporate identity, it is hoped that it can strengthen the existence of PT Yugi Indonesia in the community. Keywords—Corporate Identity; Redesign; Logo Dalam perkembangan dunia usaha yang kian pesat dibutuhkan corporate identity yang dapat mewakili karakter dari usaha, produk, atau jasa dari sebuah perusahaan. Corporate identity yang diwakili oleh logo merupakan identitas sebagai pembeda antara setiap perusahaan. Namun permasalahan timbul seiring berkembangnya zaman, perusahaan menyadari jika logo sebagai identitas perusahaan yang dibuat sebagai cerminan dari visi dan misi juga budaya pada sebuah perusahaan menjadi usang. Dari kondisi tersebut langkah untuk melakukan redesain logo identitas perusahaan dinilai menjadi pilihan yang bijak supaya logo sebagai identitas perusahaan bisa berkomunikasi secara tepat dengan apa yang diwakili oleh perusahaan. Tujuan pembahasan penelitian ini adalah terciptanya buku GSM (Grafik Standar Manual) sebagai acuan dari perancangan desain logo yang merupakan sebuah corporate identity bisa terangkai secara sitematis supaya tidak terjadi lagi kesalahan dalam pengimplementasiannya kepada setiap media visual yang digunakan perusahaan. Dalam penelitian menggunakan sebuah metode analisa permasalahan, pengumpulan data, perancangan dan konsep media desain meliputi layout kasar, layout komprehensif, serta final artwork, perancangan ulang desain logo menggunakan software adobe illustrator CC18. Dari perancangan logo sebagai corporite identity diharapkan dapat memperkuat eksistensi PT Yugi Indonesia di masyarakat. Kata Kunci—Corporate Identity; Redesign; Logo